Impact of standardized information provided by gynecologists on women's choice of combined hormonal contraception. (26th June 2013) - Machado, Rogério Bonassi; Pompei, Luciano Melo; Giribela, Arícia; de Melo, Nilson Roberto
Abstract: This prospective interventional study was designed to determine the impact of providing standardized information on different methods of combined hormonal contraception on women's selection of which method to use. A total of 952 Brazilian gynecologists were randomly selected. Each gynecologist recruited 15 consecutive patients for whom combined hormonal contraception was indicated. Each patient was asked which contraceptive method she would prefer (pill, patch, vaginal ring or injectable) before and after receiving a standardized explanation on each of these methods provided by her doctor. A total of 9507 women were included in the study. Prior to counseling, 66.5% of the women stated that they would prefer the pill, 17.9% the injectable, 8.9% the patch and 6.7% the vaginal ring. After counseling, 53.7% of the women stated that they would prefer the pill, 16.3% the injectable, 14% the patch and 16% the ring. In conclusion, the combined pill remains the most popular contraceptive method among Brazilian women; however, after receiving information on the various contraceptive methods available, the proportion of women choosing the vaginal ring or patch increased, while preference for the combined pill decreased.